Strategy consensus of networked evolutionary games based on network aggregation and pinning control - Haitao Li; Zhenping Geng; Mengyuan Qin (Games, 2025)
The computational complexity of large-scale networked evolutionary games has become a challenging problem. Based on network aggregation and pinning control methods, this paper investigates the problem of control design for strategy consensus of large-scale networked evolutionary games. The large-size network is divided into several small subnetworks by the aggregation method, and a pinning control algorithm is proposed to achieve the strategy consensus of small subnetworks. Then, the matchable condition between the small subnetworks is realized by the input-output control. Finally, some sufficient conditions as well as an algorithm are proposed for the strategy consensus of large-scale networked evolutionary games.
Keywords: 330; networked evolutionary games; network aggregation; pinning control; strategy consensus; semi-tensor product of matrices